Information systems: research, development, applications, education : 12th SIGSAND/PLAIS EuroSymposium 2019, Gdansk, Poland, September 19, 2019, proceedings /: 12th SIGSAND/PLAIS EuroSymposium 2019, Gdansk, Poland, September 19, 2019, proceedings. ([2019]) - Unknown
No abstract available